ChemInform Abstract: Recent Advances in Synthesis of Reshaped Fe and Ni Particles at the Tips of Carbon Nanofibers and Their Catalytic Applications. Issue 23 (June 2015) - Duan, Xuezhi; Ji, Jian; Qian, Gang; Zhou, Xinggui; Chen, De
Abstract Review: 90 refs.